A treatment strategy for recurrent (ankle injuries) in Muay Thai athletes - Fadhil, Saad Abbas; Khalaf, Sabah Qasim (Eximia, 2023)
Objective: An efficient solution for stabilization is the mobilization of the joints for the arthrokinematics affected by the positional defect of the CAI (i.e. chronic ankle instability). This study put to comparison the impacts of ankle dorsi flexion range of motion (DFROM) as well as dynamic balance ability (DBA) in the patients who have CAI using PJM (i.e. passive joint mobilization), a technique typically been used in previous works, and active joint mobilization (AJM), a technique which could have a greater impact on cortical excitability with the spontaneous movement. Design: rehabilitation program to treat recurrent ankle. Methods: A total of 10 players from the Iraqi clubs Muay Thai team were registered, 5 from each of the AJM and PJM groups. A total of 12 intervention sessions overall, lasting 10 mins each, were given to each participant over the course of three weeks. AJM employed angular motion of the joints to produce the patient’s voluntary motion regarding lateral malleolus posterior gliding as well as medial malleolus anterior gliding, respectively, while PJM utilized Maitland’s mobilization approach to perform mobilization of the joints with the talus in the posterior direction. Tape was used for measuring the ankle’s DFROM, and the balance system was used to assess the ankle’s DBA. Results: With the exception of DBA-right and DBA-anterior variables with regard to PJM group, considerable enhancements were seen following intervention in AJM as well as groups of the PJM. DBA-anterior, DFROM, DBA-right, and DBA-posterior, measures showed statistically significant differences between the PJM group and the AJM group. Conclusions: Joint mobilization, such as voluntary movement, was more successful thanks to the overall improvement regarding DBA and DFROM. The ankle’s neuromuscular system is significantly impacted in the case when voluntary movement is present.